Wayne Heisler Jr, The Ballet Collaborations of Richard Strauss, Eastman Studies in Music, 64 (2009) - Graydon, Philip (Journal of the Society for Musicology in Ireland, 2010)
Review of Wayne Heisler Jr, The Ballet Collaborations of Richard Strauss, Eastman Studies in Music, 64 (Rochester NY: University of Rochester Press, 2009), ISBN 978-1-58046-321-8